Analysis of Bank Syariah Indonesia (BSI) Customer Data Hacking Using Empirical Theory - Nur Shinta (CV Projurnal Mitra Publikasi, 2025)
Technological advances bring convenience in various activities, one of which is in the banking sector, where transactions can now be carried out without the need to come directly to the bank. However, this progress also presents challenges, one of which is for Islamic banking which faces cybersecurity threats, as experienced by Bank Syariah Indonesia (BSI), which was hit by a ransomware attack that caused data leakage of 15 million customers and employees and transaction disruption for almost a week. This study aims to analyze the efforts made by BSI in handling cyber threats and protecting customer data. The method used is a literature study by collecting data from various sources, such as journals, books, and research reports, and analyzing them using empirical theory. The results show that BSI improves its security system through regular training, adopts advanced security technology, conducts periodic security audits, establishes an incident response team, communicates transparently with customers, and cooperates with law enforcement to catch hackers. This research provides an overview of the importance of improving security systems and preventive measures to overcome cyber threats in the banking world.